2019
DOI: 10.1002/jcp.28313
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐microarray analysis for identification of hub genes involved in tubulointerstial injury in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a primary cause of renal failure. However, studies providing renal gene expression profiles of diabetic tubulointerstitial injury are scarce and its molecular mechanisms still await clarification. To identify vital genes involved in the diabetic tubulointerstitial injury, three microarray data sets from gene expression omnibus (GEO) were downloaded. A total of 127 differentially expressed genes (DEGs) were identified by limma package. Gene set enrichment analysis (GSEA) plots showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 86 publications
0
32
0
Order By: Relevance
“…KNG1 is a regulator of blood coagulation and belongs to the kinin‐kallikrein system. It has been reported that the activation of KNG1 plays a role in bacterial infections . Kerishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…KNG1 is a regulator of blood coagulation and belongs to the kinin‐kallikrein system. It has been reported that the activation of KNG1 plays a role in bacterial infections . Kerishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…16 For instance, folate-modified nanoparticle delivery of CCL19 activates the immune system by acting as a tumour suppressor in colon tumour. 17 Zeng et al 18 revealed that CCL19 may be involved in diabetic tubulointerstitial injury. Although the upregulation of CCL19 has been discovered in DN, the role of CCL19 in DN remains elusive.…”
mentioning
confidence: 99%
“…To further explore the function of the DEGs in AR, we used the database for Annotation, Visualization, and Integrated Discovery (DAVID) 4 to perform the GO and KEGG pathway analyses (Ogata et al, 1999;Ashburner et al, 2000). DAVID is an online bioinformatics database that is commonly used to generate systematic functional annotations about genes and proteins (Zeng et al, 2019). GO analysis consists of molecular function (MF), cellular component (CC), and biological processes (BP) analyses.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%